The formalization of interlanguage: the example of object clitic pronouns acquisition in French L2 - Amina Affes; Ismaïl Biskri; Adel Jebali (Journal of Information and Telecommunication, 2024)
ABSTRACTThe interlanguage of second and foreign language French learners presents certain patterns that offer a formal framework within the context of the Applicative Combinatory Categorical Grammar. These patterns manifest in the acquisition of object clitics which presents considerable difficulties for French second language learners. To address this, we thoroughly analysed the object clitic pronouns that appeared in a corpus of texts by examining the different facets of these pronouns. A formal analysis was then proposed. The objective of this research is to establish an automated system for processing learners’ interlanguage in terms of the ACCG.